A disaggregated freight transport market model based on agents and fuzzy logic. Issue 1 (23rd December 2019) - Reis, Vasco
Abstract : Disaggregated modelling approaches, such as agent-based, have been successfully used to model freight transport markets. However, the maturity of published models is still relatively low. This paper proposes a novel agent-based model of a freight transport market. The model contains several new features. The decision-making process of individual agents is simulated through a normative stepwise approach using fuzzy set theory and accumulated market knowledge. Agents interact through simulated auctions of transport contracts. A dynamic price calculation mechanism has been devised to simulate agents' specific pricing strategies. A distinguishing feature is that it can be used to assess the influence of agents' market-related measures and behaviour on their competitiveness and on the respective transport chain. A synthetic market was calibrated to demonstrate its capabilities and limitations. The paper concludes with a set of directions for future research work.